The effect of heating rate and sintering temperature on glass ceramic composite at different filler loading - Salleh, Nur Syahidah (2016)
The present work aims to develop fundamental information for the fabrication of glass ceramic composite (GCC) from recycled soda lime silicate (SLS) glass integrated with high loading of filler which is spent bleach earth (SBE). The aim of this study is to investigate the effects of different heating rate and sintering temperature on physical properties, microstructure and mechanical properties of GCC at different SBE loading. The recycled SLS glass and SBE were prepared by sieving to particle size < 45 μm and removing the oil in SBE by sonification process, respectively. The particle size distribution for both powders was determined using Laser Particle Size Analyzer (LPA). The main elements of recycled SLS glass were silicon dioxide (SiO2), and calcium oxide (CaO), while the main elements of SBE were silicon dioxide (SiO2) and aluminium oxide (Al2O3) determined via X-ray Fluorescence (XRF) analysis. Glass transition temperature (Tg) of recycled SLS glass was observed around 514 ºC. The compositions were selected based on high SBE loading which were SLS to SBE; 60:40, 55:45 and 45:55 wt. %. The type of sintering involved for 60:40 and 55: 45 wt. % of SLS to SBE was viscous flow sintering (VFS). Meanwhile for 45:55 wt. % of SLS to SBE, the sintering type involved was liquid phase sintering (LPS). The GCC was then formed using uniaxial dry pressing method with pressure at 2.5 tonnes for square mold and at 8 tonnes for rectangular mold. In the first part, the GCC sample was sintered at 700 ºC with heating rate of 2, 4, 6, and 8 ºC/min. Observation on crystalline phases showed that main crystalline phases appeared were quartz (SiO2) and wollastonite (CaSiO3). Increasing the heating rate did not give remarkable results of physical properties on green GCC. Microstructure observation revealed the presence of pores at minimal quantity. In this parameter, 2 ºC/min was chosen as an optimum heating rate. In the second part, the GCC was sintered at different sintering temperature of 750 ºC and 850 ºC. The results showed distinctive differences in physical properties, phases, and microstructure. This indicates that the composite was strongly influence by the sintering temperature. Increasing the sintering temperature showed high percentage of shrinkage, low percentage of porosity, and water absorption. The main phases appeared were quartz (Si02), wollastonite (CaSi03), cristobalite (Si02), and carneigeite (NaAlSiO4). Crystalline phases showed high intensity and additional of new phases when the sintering temperature increased. Observation on microstructure disclosed more uniform and densified microstructure. An optimised green GCC of 45 wt. % SBE was successfully fabricated at sintering temperature of 850 ºC and heating rate of 2 ºC/min. The mechanical properties of hardness was 0.12 GPa and flexural strength of 9.50 MPa. A good prospect of addition some binder should be further explored on the fabrication of glass ceramic composite with high loading of SBE.